Idiopathic Intracranial Hypertension in Children: Clinical Presentations and Management - Aboul Enein, Hisham A. (Medknow Publications, 2008)
BACKGROUND: Idiopathic intracranial is common in adults, particularly obese young women, but also occurs in children and adolescents. AIM: Clinical presentation of idiopathic intracranial hypertension in the pediatric population and how the presenting signs and symptoms may be different from those seen among adult patients. RESULTS: This study is a prospective study conducted in the Alexandria Medical School, Egypt, between the periods starting from January 2003 till December 2007. Ten patients were included in this study, 9 patients were treated with repeated spinal taps while only one patient necessitated insertion of a theco-peritoneal shunt. CONCLUSION: Idiopathic intracranial hypertension may occur in children as among adults. If diagnosed early, visual acuity can be saved with proper management.